Atomic scale structural analysis of liquid immiscibility in binary silicate melt: A case of SiO2‒TiO2 system. (15th September 2020) - Zhang, Cuiyu; Ge, Xuan; Hu, Qiaodan; Yang, Fan; Lai, Pingsheng; Shi, Caijuan; Lu, Wenquan; Li, Jianguo
Abstract: Thermodynamic/dynamic modeling of liquid immiscibility in silicates is seriously hindered due to lack of in situ investigation on the structural evolution of the melt. In this work, atomic-scale structural evolution of a classic binary silicate immiscible system, SiO2 –TiO2, is tracked by in situ high energy X-ray diffraction (HE-XRD). It is found that both the configuration of [SiO] and the polymerization between them are closely coupled with embedment and extraction of the metallic cations (Ti 4+ ). [SiO] monomer goes through deficit-oxygen and excess-polymerization before liquid‒liquid separation and enables self-healing after liquid‒liquid separation, which challenges the traditional cognition that [SiO4 ] monomer is immutable. Ti 4+ cations with tetrahedral oxygen-coordination first participate in the network construction before liquid separation. The four-fold Ti–O bond is broken during liquid separation, which may facilitate the movement of Ti 4+ across the Si–O network to form TiO2 -rich nodules. The structural features of nodules were also investigated and they were found highly analogous to that of molten TiO2, which implies a parallel crystallization behavior in the two circumstances. Our results shed light on the structural evolution scenario in liquid immiscibility at atomic scale, which will contribute to constructing a complete thermodynamic/dynamic framework describing the silicate liquid immiscibility systems beyond current models.